Methods and approaches of determining the boundaries of agglomerations (basic case Kharkiv region) - Kateryna Kravchenko; Kostiantyn Niemets; Kateryna Sehida; Lyudmyla Niemets; Olha Suptelo (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2020)
Changes in social relations in Ukraine, its transition to a post-industrial society, structural changes in regional development lead in modern conditions to changes in the territorial organization of society, which directly affects the trends of regional development. The highest form of territorial organization of society are agglomerations – uban agglomerations. Defining the boundaries of agglomerations is an important step in the process of studying agglomerations and managing regional development, because it is necessary to clearly understand the territory to which the administrative influence should extend and the number of city councils whose activities should be coordinated in implementing regional policy. The purpose of this work is to analyze the existing methods, approaches and techniques for determining the boundaries of agglomerations, development of an algorithm for establishing the boundaries of agglomerations and its testing on the materials of the Kharkiv region. The main theoretical and methodological starting points of delimitation of agglomeration boundaries are presented, approaches, methods and techniques, their quantitative and qualitative criteria, indicators, etc. are determined. The author 's algorithm for establishing agglomeration boundaries is substantiated, initial positions, key indicators, coefficients and indices are indicated. The proposed algorithm was tested on the materials of Kharkiv region. It is established that the Kharkiv agglomeration is monocentric and well formed. The development coefficient of the Kharkiv urban agglomeration is 30.7, the agglomeration coefficient is 0.13, the agglomeration index is 0.25, which confirms the high level of development of this agglomeration and the significant polarizing effect of the city of Kharkiv. The applied indicators of concentration and population density, transport accessibility, allowed to establish that the Kharkiv agglomeration has a powerful organizational center of development - the city of Kharkiv, the polarizing effect of which is more pronounced in two districts – Kharkiv and Dergachiv, which form the central zone of the agglomeration. The center of the agglomeration is connected with remote centers of peripheral areas by radial-radial connections by transport and other types of connections, which forms an external zone consisting of Bohodukhiv, Valkiv, Vovchansk, Zmiiv, Zolochiv, Novovodolazk, Pecheneg and Chuhuiv districts. Based on the study, based on the principle of superposition, the author's vision of delimitation of the Kharkiv agglomeration in 2019 is presented. The zone of influence of organizational functions of the center extends to a radius of 70 km, but there are significant territorial disparities in the center and periphery. The city of Kharkiv assumes most of the functions: administrative, economic, social, infrastructural and recreational, which to some extent hinders the development of small towns that are part of the agglomeration. The strengths of the Kharkiv agglomeration are indicated, as well as the priority directions of development are singled out. Given that the Kharkiv agglomeration is monocentric, and within it, as in the region there is a sharp uneven development of the center and periphery, effective management and addressing the hypertrophied development of the city, spatial planning and infrastructure development will alleviate this situation and facilitate the transition of the region. to the polycentric model of spatial organization, respectively, and the reduction of territorial disparities in the level and quality of life of the population of the Kharkiv region.